Inclusion of Three-Vessel View in Routine Fetal Cardiac Screening - Subedi, K; Chataut, D; Khanal, UP; Ansari, MA; Pradhan, S (Nepal Journal of Obstetrics and Gynaecology, 2014)
Aims: The purpose of this study was to study the feasibility of inclusion of 3-vessel view (3-VV) of the fetal upper mediastinum in routine fetal anomaly screening; and to study the size relationship of these vessels namely, main pulmonary artery (MPA), ascending aorta (AA) and the superior venacava (SVC) in fetuses between 17 and 24 weeks of pregnancy by antenatal ultrasound. Methods: This was a prospective cross sectional study involving 106 pregnant ladies between 17 and 24 weeks of gestation. The time burden to the examination due to addition of 3-VV in routine anomaly screening was recorded. The relationships of the three great vessels of the fetal upper mediastinum were studied and their diameters were obtained. Regression equations were used to construct the reference ranges for all the parameters of statistical significance. Results: The 3-VV could be easily obtained in all but eight patients within five minutes (the difficulty in these eight patients was due to fetal position). The MPA, AA and SVC were aligned in a straight line from left to right respectively, the MPA being the largest vessel, the SVC being the smallest vessel and the AA having an intermediate diameter. All of these three vessels showed significant correlation of size with advancing gestational age. Conclusions: 3-VV is easily obtained in fetuses at the time of routine anomaly screening. This should be routinely included in the screening ultrasound of fetal heart along with the four-chamber view to detect the anomalies of the outflow tract. DOI: http://dx.doi.org/10.3126/njog.v9i1.11197 NJOG 2014 Jan-Jun; 2(1):82-86